Efficient scale of prefectural government in China - Mototsugu Fukushige; Yingxin Shi (China Finance and Economic Review, 2016)
Background: China has five layers of government including the central government. Recently, some prefectural governments meet fiscal distress. Methods: We investigate the effects of urban and rural populations and area sizes on the expenditures of the prefecture-level local government by estimating quintile regression. Results: At around 220,000 people, per capita local government expenditure for urban populations is minimized in our simulation. The expenditure for rural populations is proportional to the population size. The expenditure in accordance with the areas is also proportional to the area size. Conclusions: The cost structure is the reason why China's recent rapid urbanization increases prefectural government's fiscal distress.
Keywords: H40; H72; R51; 330; Efficient scale; Local government; Quantile regression; China